Firing Temperature Effect on the Thermo-structural Properties of Clay for Refractory Purposes: A Comparative Study on Nigerian Clay Deposits - Obialo, Nwokeocha Tochukwu; Okolie, Paul Chukwulozie; Odeh, Calistus Princewill; Okoye, Chibuzo Ndubuisi; Uzodinma, Madumere Augustine (Budapest International Research and Critics University, 2025)
A comparative study on firing temperature effect on the thermo-structural properties of clay for refractory purposes, have been carried out on three Nigerian clay deposits (Mgbom, Amokwe and Amagu Ishiagu clay deposits). Three firing temperatures; 900, 1100 and 1200oC were considered in the study. Standard clay preparation procedures were employed in setting up the experiment, these include; crushing, soaking, drying, grinding, sieving, blending and moulding. Six refractory property tests (linear shrinkage, bulk density, apparent porosity, water absorption, thermal shock resistance and refractoriness) were carried out on the prepared clay according to ASTM standards. For the purpose of microstructural characteristics, the Scanning Electron Microscope (SEM) test was also conducted. The test result gave a 27.26 - 42.53N/mm2, 4.09 – 9.27% 1.66 – 2.07g/cm3 1.01 – 15.65% 19-28 cycles for modulus of rupture, linear shrinkage, bulk density, apparent porosity and thermal shock respectively. The microstructural analysis showed a level of similarity between that of Mgbom and Amagu while that of Amokwe gave a number of visible pores. From the analysis of the obtained results 1200oC firing temperature was recommended among the studied temperatures.